Identifikasi Potensi Mineralisasi Emas di Kecamatan Sangir menggunakan Data Geomagnetik EMM 2017 - Intan Fitri; Arif Budiman (Jurnal Fisika Unand, 2026)
Indonesia is a country with significant potential for gold mineral resources, particularly in areas along the Sumatran magmatic belt. This study aims to identify the potential distribution of gold mineralization in Sangir District, South Solok Regency, using secondary geomagnetic data. The data used is the Enhanced Magnetic Model (EMM) 2017 model obtained from the National Oceanic and Atmospheric Administration (NOAA). Data processing was carried out through the stages of IGRF correction, calculation of total magnetic anomalies, separation of regional and residual anomalies and reduction-to-pole transformation (RTP) using Oasis Montaj software. The results show that the residual anomaly after reduction to the pole ranges from -1.0935 to 1.1861 nT. Based on local geological conditions, zones with low magnetic anomalies that develop in the central to western parts of the study area are interpreted as alteration and fracture zones that have the potential to become hydrothermal fluid movement pathways. The zone with moderate to high magnetic anomalies that developed in the eastern, east-central, and southeastern parts of the research area is interpreted as a response from high magnetic rocks associated with sulfide minerals (pyrite) and porphyry systems, so that the zone is identified as a prospective zone that has the potential to contain gold mineralization.